Titanium-containing Blast Furnace Slag Produced Titanium-silicon-aluminum Alloy by Aluminothermic Reduction - Mantang DING (Kuangchan zonghe liyong)
This is an article in the field of metallurgical engineering. At the protection of argon gas, titanium-containing blast furnace slag produced titanium-silicon-aluminum alloy by aluminothermic reduction. The test result shows at 1 500 ℃, at the protection of argon gas, when aluminum powder accounts for 30%～40% of blast furnace slag, lime accounts for 5%～15% and fluorite ≥ 5%, the alloys obtained by reduction are mainly titanium-silicon phase, aluminum-silicon phase, titanium phases. In the alloy, the content of titanium, silicon, aluminum were 35%～40%, 26%～33%, 23%～32%, respectively. The recoveries of titanium, silicon, aluminum were 73%～88%, 84%～95%, 67%～77%, respectively.